Re-esterified DHA improves ventilatory threshold 2 in competitive amateur cyclists - Ávila-Gandía, Vicente (J Int Soc Sports Nutr, 2020)
BACKGROUND: Fish oils were studied as ergogenic aids in a number of mixed physical trial designs showing promising results. However, the heterogeneous purity of the studied supplements, combined with the variety of physical tests employed call for more studies to confirm these findings, ideally with standardised supplements. Our aim was to test a supplement highly concentrated in DHA (DHA:EPA ratio equal to approximately 8:1) on a maximal cycling test to elucidate performance improvements mainly due to DHA. METHODS: A double-blind, placebo controlled, randomised balanced, parallel design, in competitive amateur cyclists was employed. They were all male, older than 18 years old, with training routine of 2 to 4 sessions per week lasting at least one hour each. A ramp cycling test to exhaustion with a subsequent 5 min recovery phase was employed before and after treatment to analyse aerobic metabolism and lactate clearance after the bout. After 30 days of supplementation with 975 mg of re-esterified DHA, the thirty-eight cyclist who completed the study were finally included for statistical analysis. RESULTS: Mean power output at ventilatory threshold 2 (VT2) improved after DHA supplementation both as absolute (△DHA versus △PLA: 6.33–26.54 Watts; CI 95%) and relative (p=0.006) values, paralleled with higher oxygen consumption at VT2 both for absolute (DHA 2729.4 ±304.5, 3045.9 ±335.0; PLA 2792.3 ±339.5, 2845.5 ±357.1; ml·min(−1) baseline versus post p=0.025) and relative values (DHA 36.6 ±5.0, 41.2 ±5.4; PLA 37.2 ±5.7, 38.1 ±5.2; ml·kg(−1)·min(−1) baseline versus post p=0.024). Heart rate recovery rate improved during the recovery phase in the DHA group compared to PLA (p=0.005). CONCLUSION: DHA is capable of improving mean power output at the ventilatory threshold 2 (anaerobic ventilatory threshold) in amateur competitive cyclists. It is unclear if these findings are the result of the specific DHA supplement blend or another factor.